Aprender música fazendo arranjo a quatro mãos por duas estudantes de piano do nível técnico do Conservatório Estadual de Música Cora Pavan Capparelli de Uberlândia/MG - Luz, Jane Finotti Rezende (2013)
The object of this study is the relationship between learning music and making a fourhand piano arrangement. This research was based on an understanding of music and of the ways of learning and making arrangements as a sociocultural phenomenon; and considered the way subjects choose, experience and create music. The question that I set out to investigate was: How two students at the Technical State Conservatory of Music Cora Pavan Capparelli of Uberlândia/MG could learn music making a four-hand piano arrangement? Other questions unfolded in the process of approaching the empirical field: Is the arrangement a creative process? In what situations and contexts of arrangement creation can music learning be uncovered? What modes of learning can be observed? These questions represent some of my main concerns and interests regarding this theme. The subjects who collaborated with the research are piano students at the State Conservatory of Music Cora Pavan Capparelli in Uberlândia (CMCPC) who agreed to participate. To understand these relationships there was a dialogue between Music Education, other areas of knowledge and the musical practice of making four-hand arrangements. This study was based on articulation between the theoretical concepts related to the research theme with the data brought from the empirical field so that my reflections could be grounded in a more meaningful gaze towards the way students learn while making a four-hand piano arrangement. It took as a point of departure my experience as a piano teacher. Reviewed in this final report, it proved to be open to new questions for future research, since I envisioned that the categories constructed here can be extended and crossed by diverse contextual dimensions of music learning. The unique experience that I lived while doing this research reinforced the need for a critical analysis of youth training in the realm of the musical creation practice. \"Learning during research\" was what excited me the most in this activity. I could understand the broader senses in which the concept of learning works and, through scientific research, reflect more about myself performing teaching activities. The data results show learning modes with dialogical, emotional, intellectual and reflexive responses related to the meanings created in the course of making the arrangement. The relevance of this research is to give a contribution to the advancement of an environment at Conservatório which creates possibilities of a broader intervention of Music Education.